Dementia-related stigma in physicians: a scoping review of stigma-reduction interventions - Warren, Alison; Wynia, Zan (Frontiers in Dementia, 2025)
IntroductionDespite progress in dementia diagnosis and treatment, physician-held stigma remains a significant barrier to early recognition and effective care. Stigmatizing attitudes among healthcare professionals can negatively impact diagnosis rates, clinical interactions, and care quality for people living with dementia.MethodsThis scoping review was conducted following Arksey and O’Malley’s framework. Peer-reviewed literature from 2014 to 2024 was systematically reviewed to identify and evaluate interventions aimed at reducing dementia-related stigma among physicians. A total of 14 studies met inclusion criteria, examining educational, skill-building, and person-centered approaches.ResultsInterventions included brief workshops, online modular training, and interdisciplinary methods integrating person-centered frameworks and behavior management tools. Validated outcome measures used in the studies included the Alzheimer’s Disease Knowledge Scale (ADKS), the Dementia Negative Stereotype Scale (DNS), and the General Practitioners Confidence and Attitude Scale for Dementia (GPACS-D). Across studies, interventions were found to improve clinical confidence, reduce negative stereotypes, and enhance care quality.DiscussionFindings highlight the importance of culturally sensitive and interdisciplinary interventions to address stigma, improve clinical confidence, and enhance care quality, particularly in low-resource settings. Notable gaps remain in understanding the long-term impact and scalability of such interventions. This review aims to contribute a deeper understanding of the barriers and facilitators to implementing dementia care practices, offering a conceptualization for enhanced physician education and improved health outcomes for persons with dementia. We offer recommendations for future research to develop tailored strategies that support stigma reduction and improve care delivery.